Prognostic implications of septal hypertrophy in patients with heart failure with mildly reduced ejection fraction - Abel, Noah; Schupp, Tobias; Abumayyaleh, Mohammad S. A.; Schmitt, Alexander; Reinhardt, Marielen; Lau, Felix; Ayoub, Mohamed; Mashayekhi, Kambis; Akın, Muharrem; Rusnak, Jonas; Akın, Ibrahim; Behnes, Michael (Journal of Clinical Medicine, 2024)
Cardiac remodeling is frequently observed in patients with heart failure (HF) and serves as an indicator of disease progression and severity. Septal hypertrophy represents an aspect of remodeling that can be easily assessed via an echocardiographic measurement of the interventricular septal end diastole (IVSd), but it has not been evaluated for its prognostic value, particularly in patients with heart failure with mildly reduced ejection fraction (HFmrEF). We retrospectively included 1881 consecutive patients hospitalized with HFmrEF (i.e., a left ventricular ejection fraction of 41-49% and signs and/or symptoms of HF) at one institution during a study period from 2016 to 2022. Septal hypertrophy, defined as an IVSd > 12 mm, was prevalent in 34% of the HFmrEF patients. Although septal hypertrophy was not associated with all-cause mortality at 30 months (median follow-up) (HR = 1.067; 95% CI: 0.898-1.267; p = 0.460), it was associated with an increased risk of hospitalization due to worsening HF at 30 months (HR = 1.303; 95% CI: 1.008-1.685; p = 0.044), which was confirmed even after multivariable adjustment (HR = 1.340; 95% CI: 1.002-1.792; p = 0.049) and propensity score matching (HR = 1.399; 95% CI: 1.002-1.951; p = 0.048). Although septal hypertrophy was not associated with the risk of all-cause mortality in patients with HFmrEF, it was identified as an independent predictor of long-term HF-related rehospitalization.
Gesehen am 15.10.2024